Agent-Oriented Software Engineering Reflections on Architectures, Methodologies, Languages, and Frameworks - Shehory, Onn.; Shehory, Onn.; Sturm, Arnon.; Sturm, Arnon. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
With this book, Onn Shehory and Arnon Sturm, together with further contributors, introduce the reader to various facets of agent-oriented software engineering (AOSE). They provide a selected collection of state-of-the-art findings, which combines research from information systems, artificial intelligence, distributed systems, and software engineering and covers essential development aspects of agent-based systems. The book chapters are organized into five parts. The first part introduces the AOSE domain in general, including introduction to agents and the peculiarities of software engineering for developing MAS. The second part describes general aspects of AOSE, like architectural models, design patterns, and communication. Next, part three discusses AOSE methodologies and associated research directions, and elaborates on Prometheus, O-MaSE, and INGENIAS. Part four then addresses agent-oriented programming languages. Finally, the fifth part presents studies related to the implementation of agents and multi-agent systems. The book not only provides a comprehensive review of design approaches for specifying agent-based systems, but also covers implementation aspects such as communication, standards, and tools and environments for developing agent-based systems. It is thus of interest to researchers, practitioners, and students who are interested in exploring the agent paradigm for developing software systems.